60 let pozneje – pomen analize govorjenega diskurza: Mojca Smolej (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
60 Years Later – The Significance of Spoken Discourse Analysis. This paper gives a brief overview of the beginnings of research on spontaneous spoken language in Slovenia. One of the first papers was published almost 60 years ago by Breda Pogorelec. The first section of the paper delves into the beginnings of spoken language research, while in the second section some considerations are made as to why it is necessary to continue and build on previous research. They are presented from the point of view of the descriptive grammar of both spoken and written (literary) language. Understanding the regularities of spoken language can help to understand and resolve some unclear grammatical descriptions (rules) of literary language. Insufficiently defined or described grammatical regularities of the literary language can therefore cause problems both at the level of teaching Slovene as a first and second/foreign language and at the level of language use by general speakers (i.e. non-linguists).